Plasma jet generation by flyer disk collision with massive target - Kasperczuk, Andrzej; Pisarczyk, Tadeusz; Borodziuk, Stefan; Gus'kov, Sergey Yu.; Ullschmied, Jiri; Krousky, Edward; Masek, Karel; Pfeifer, Miroslav; Rohlena, Karel; Skala, Jiri; Kalal, Milan; Limpouch, Jiri; et al. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
In this paper, results from experiments with Al flyer targets (disks with a diameter of 300 mm and a thickness of 6 mm) accelerated at first to high velocities by PALS iodine laser pulses (with an energy of 130 J, pulse duration of 400 ps, a wavelength of 1.315 mm, and laser spot diameter of 250 mm), subsequently creating craters after their collisions with massive Al targets (placed at a distance of the order of 200 mm) are presented. To measure the plasma density evolution a three frame interferometric system was employed. The experimental results demonstrate that the flyer disk–massive target collision generates an axial plasma jet corresponding to a flat shock wave propagating in a massive target. This form of the shock wave was deduced from a crater trapezoidal shape which was reconstructed by means of crater replica technique.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 73-82
Keywords: optyka; ablative acceleration; plasma jet; flyer disk; interferometry; macroparticle; double target; linear electron density; crater; shock wave